Forming sustainable educational partnerships - Maes, Sue C.; Anderson, Dawn; Peters, Jim (Kansas State University, 2010)
Higher education institutions often compete with each other for students and faculty, offering similar courses while at the same time trying to market their institution’s strengths to best effect. Yet, the challenge of sustainability requires such diverse skills and backgrounds that there is great opportunity in the diversity of Kansas higher education institutions. This panel discussion will explore ways in which the variety of schools in Kansas can develop partnerships, whether new courses, conferences, degrees, or more, that leverage the different strengths of different institutions in collaboratively addressing complex sustainability educational needs in Kansas.
Keywords: Collaboration; Education partnerships